2012
DOI: 10.1155/2012/346358
|View full text |Cite
|
Sign up to set email alerts
|

Phi-Functions for 2D Objects Formed by Line Segments and Circular Arcs

Abstract: We study the cutting and packing C&P problems in two dimensions by using phi-functions. Our phi-functions describe the layout of given objects; they allow us to construct a mathematical model in which C&P problems become constrained optimization problems. Here we define for the first time a complete class of basic phi-functions which allow us to derive phi-functions for all 2D objects that are formed by linear segments and circular arcs. Our phi-functions support translations and rotations of objects. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 14 publications
0
27
0
5
Order By: Relevance
“…For the prescribed models, most are commonly used to analyze simplified polygons fixed in a specific orientation denoted as phi-objects [74]. Similar phi-object models are presented in [75,76]. In FFF printing processes, the operator commonly selects the build orientation based on metrics related to print quality, dimensional stability and mechanical properties.…”
Section: Areas Of Improvement and Comparison To Other Technologiesmentioning
confidence: 99%
“…For the prescribed models, most are commonly used to analyze simplified polygons fixed in a specific orientation denoted as phi-objects [74]. Similar phi-object models are presented in [75,76]. In FFF printing processes, the operator commonly selects the build orientation based on metrics related to print quality, dimensional stability and mechanical properties.…”
Section: Areas Of Improvement and Comparison To Other Technologiesmentioning
confidence: 99%
“…In order to model an arbitrary object, the object needs to be decomposed into basic and primitive objects. Chernov et al (2012) provides a decomposition algorithm for this purpose. They define four types of basic objects.…”
Section: Phi-objects For Modelling Forbidden Regionsmentioning
confidence: 99%
“…These are (i) a convex polygon ( Figure 5(a)), formed by an intersection of three or more half-planes, (ii) a circular segment (Figure 5(b)), as an intersection of a circle and a half-plane, (iii) a hat ( Figure 5(c)), formed by an intersection of a complement of a circle and two half-planes that corresponding boundaries are tangent to the circle and (iv) a horn ( Figure 5(d)), an intersection of a circle, a complement of a circle and a half-plane. Chernov et al (2012) showed that any arbitrarily shaped composed object bounded by circular arcs and line segments can automatically be decomposed into a set of defined basic objects by the given algorithm.…”
Section: Phi-objects For Modelling Forbidden Regionsmentioning
confidence: 99%
“…A tutorial covering the core geometric methodologies currently applied by researchers in cutting and packing of irregular shapes is presented by [4]. Tools of mathematical modeling of arbitrary object packing problems are given by [6,10,11]. Complexity investigations for cutting and packing problems can be found in [7,9,12,20] .…”
Section: Related Workmentioning
confidence: 99%
“…The objectives we consider here are linear { 2 3 4 6 , , , F F F F } or quadratic { 1 5 , F F }. The phi-functions in (5) are composed of min -and max -combinations of linear and\or non-linear functions including sin -and cos -terms [11]. System 0 λ ≥ , involves linear and\or non-linear functions including sin -and cos -terms.…”
Section: Mathematical Modelmentioning
confidence: 99%